Взаємодія просодичних засобів у забезпеченні цілісності тексту іспанської казки та їх вплив на її сприйняття - Наваренко, І.А. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The task of this paper is to analyse and estimate prosodic regularities in Spanish tales. The analysis reveals the internal dynamics as the interplay of various prosodic features within its topic structure. It was determined that the prosodic organization of Spanish tales as a part of its communicative strategy reflects the correlation between the suprasegmental level units of the Spanish tales whose effectiveness is assured by the prosodic parameters harmonization.